PERUBAHAN WARNA DAN LAPISAN FINISHING LIMA JENIS KAYU AKIBAT PENCUACAAN - Krisdianto; Esti Rini Satiti; Achmad Supriadi (BRIN Publishing, 2018)
The increase use of wood products for outdoor arises from warmth color and amenity properties of wood. However, wood is naturally degraded in term of color changes and finishing layer percentage after outdoor exposure. This paper presents wood color change and finishing layer durabillity after one year outdoor exposure. Five lesser known wood species from Riau were coated transparently using acrylic, enamel, polyurethane, ultran lasur ultra violet (UV), and ultran politur P-03 UV prior to outdoor exposure. Wood color differences were assessed according to CIELab system and coating film coverages were digitally analyzed by ImageJ software. The result showed that natural wood color turned into greyish pale after one year outdoor exposure. Color changes are relatively high in the first month then moderate and little changes every month there of. Finished layer wood samples were more resistant to weathering than unfinished surfaces. Finishing material of enamel (ET), lasur (LSR), and P03 (PP) experienced better coverage than acrylic and polyurethane finish. Finishing layer is gradually degraded, then re-finishing is necessary for optimal outdoor protection. Relationships between finishing coverage and color change showed medium correlation, where the greater finishing coverage, the greater the color changes.